Evaluation of the antioxidant and in vitro cytotoxic activity of Averrhoa carambola, Aegle marmelos and Spondias pinnata leaf extracts - Zaman, Anahita Tanzia (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2015.